Out-of-plane response of arching masonry walls to static loads. (15th December 2019) - Edri, Idan E.; Yankelevsky, David Z.; Rabinovitch, Oded
Highlights: The static response of arching masonry walls to out-of-plane loading is analyzed. The MDOF model refers to rigid blocks interconnected by nonlinear springs. The model formulation considers geometrical and material nonlinearities. The mortar inelastic-nonlinear behavior and its effect on the response is shown. Comparisons between the model and test results show good agreement. Abstract: This paper aims at characterizing the response of arching masonry walls to out-of-plane static loading. An analytical multi-degree-of-freedom model is presented aiming at modeling the nonlinear out-of-plane behavior of arching masonry walls. The model combines physical modeling tools with a formulation that applies variational principles and equilibrium conditions, boundary and continuity conditions, geometrically nonlinear kinematics, and nonlinear constitutive laws. The latter take into account the nonlinear response in compression and in tension, including cracking and inelastic response of the joints. The model refers to one-way flexural action of unreinforced masonry walls. The masonry units are modeled as rigid bodies, whereas the mortar joints are represented by arrays of springs with nonlinear kinematics and nonlinear constitutive behavior. A series of numerical examples that explore the capabilities of the model, reveal various aspects of its physical behavior and compare the analysis with experimental results reported in the literature are presented. The examined aspects include the cracking process, the development of the arching mechanism, and the effect of inelastic behavior of the mortar material on the response. The combination of the above provides a deeper look into the unique and complex physical behavior of arching walls and sets a modeling approach for its quantitative assessment.